2011
DOI: 10.1007/s13204-011-0050-z
|View full text |Cite
|
Sign up to set email alerts
|

The novel and economical way to synthesize CuS nanomaterial of different morphologies by aqueous medium employing microwaves irradiation

Abstract: CuS nano/submicro materials with different morphologies were synthesized with spherical, tubular, leaflike and strip type structures in a simple aqueous system under microwave irradiation and sunlight and employing Cu (CH 3 COO) 2 , CuSO 4 Á5H 2 O, CuCl 2 , and as copper source and H 2 NCSNH 2 , Na 2 S 2 O 3 Á5H 2 O and CH 3 CSNH 2 as sulfur sources. The starting materials were used without assistance of any surfactant or template. An X-ray powder diffraction pattern confirms that the product was CuS with hexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…7. This initial mass loss involves multiple transitions occurring during the heating process (Nafees et al 2011(Nafees et al , 2012. As observed from differential thermogravimetric (DTGA) curve, dehydration takes place first resulting in the removal of water of crystallization around 100°C while a hump between 200 and 250°C corresponds to (2017) A sharp endothermic peak observed in DSC curve at 880°C indicates melting of PbO without the involvement of any mass loss as supported by TGA and DTGA curves.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…7. This initial mass loss involves multiple transitions occurring during the heating process (Nafees et al 2011(Nafees et al , 2012. As observed from differential thermogravimetric (DTGA) curve, dehydration takes place first resulting in the removal of water of crystallization around 100°C while a hump between 200 and 250°C corresponds to (2017) A sharp endothermic peak observed in DSC curve at 880°C indicates melting of PbO without the involvement of any mass loss as supported by TGA and DTGA curves.…”
Section: Resultsmentioning
confidence: 85%
“…Utilization of PbO and PbS nanostructures for potential applications is strongly subjected to their thermal stability in air and inert atmosphere. Structural phase transitions, oxidation, and recrystallization occur rapidly in metal sulfides upon small increments of temperature (Nafees et al 2011(Nafees et al , 2012(Nafees et al , 2015Qadri et al 2003;Sadovnikov et al , 2011. Therefore, a better understanding of oxidation temperature/resistance and thermal stability of PbO and PbS is crucial for realizing potential applications these materials promise.…”
Section: Introductionmentioning
confidence: 99%
“…However, copper sulfide has multifarious crystal chemistry due to its capability to form a variety of stoichiometric copper sulfide compounds. Jumble phase copper sulfides are generally synthesized in many synthetic means (Yang and Xiang 2005;Zou et al 2007;Tan et al 2005;Zhu et al 2007;Wang et al 2007;Zhang et al 2004;Nafees et al 2011). Ni et al (2004) reported the formation of CuS nanotubes using aqueous phase technique with different starting materials of diameter ranging from 350 to 1,000 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In the other hand, thiosulfate has ability to release H 2 S by reacting with H 2 O, then H 2 S react with copper ions and make CuS as black nanoparticles [56][57][58]. A reducing agent was needed to produce S 2À which EG helped.…”
Section: Synthetic Mechanismmentioning
confidence: 99%